First genome sequence of Aeromonas hydrophilia novel sequence type 658 strain isolated from livestock in South Africa. (March 2021) - Ramsamy, Yogandree; Amoako, Daniel G.; Abia, Akebe Luther King; Allam, Mushal; Ismail, Arshad; Mtshali, Phillip Senzo; Mlisana, Koleka P.; Essack, Sabiha Y.
Abstract: Objectives: The underlying resistance mechanisms, defence systems, mobilome, virulome, clonality and global phylogenetic relationship of a novel sequence type (ST) 658 Aeromonas hydrophilia (A34a) isolated from a pig abattoir in South Africa was determined using whole-genome sequence (WGS) technology. Methods: Following isolation on chromogenic agar (CHROMID® CARBA SMART), microbial identification and antibiotic susceptibility testing were performed using a VITEK®2 platform. Genotyping involved WGS performed with an Illumina MiSeq platform. Results: The antibiotic resistome agreed with the resistance phenotype of the isolate and included antibiotic resistance determinants for β-lactams ( bla CPHA3 and bla OXA-724 ). BLASTn analysis of resistome-encoding contigs affirmed chromosomally-mediated resistance. BURST algorithmic analysis identified the novel ST658 as a satellite variant. Virulome analysis predicted virulence genes of Aeromonas whose expression are critical for establishing infection in the host. Global phylogenomic analyses showed strain A34a is closely related to two international isolates from Sri Lanka (Ae25) and the USA (RU34A), although there is little to suggest that it was imported from abroad. Conclusion: This is the first report on the genomic analysis of a novel ST658 A. hydrophilia, offering useful insights into its pathogenicity and global phylogenetics.